A cost-utility analysis of obeticholic acid treatment and value of information analysis in the Philippines - Estacio, Jenerose Alcantara (Animo Repository, 2024)
Non-alcoholic steatohepatitis (NASH) is a concern; however, analytic models for decision-making for case management and health promotion are highly uncertain. Utilizing the Value of Information (VOI) framework, this research aims to assess the influence of parameter uncertainties. It aims to: (1) assess the cost-effectiveness of Obeticholic Acid (OCA) treatment among middle- aged adult Filipino NASH patients and (2) assess the impact of enhancing data quality in the developed analytic model (Expected Value of Perfect Information, EVPI). The analysis, conducted with a PHP 1 million per QALY threshold, found OCA treatment not cost-effective, signaling the need for further exploration. Limitations acknowledged include reliance on data from other countries, emphasizing the importance of gathering local data on disease prevalence, transition probabilities, and costs to enhance model accuracy. Sensitivity analyses suggest focusing future research on OCA's effectiveness in early NASH stages while exploring higher willingness-to-pay (WTP) thresholds, which may reveal potential cost-effectiveness, requiring further investigation into implementation feasibility within the Philippine healthcare system. Furthermore, the study underscores the value of reducing uncertainty, emphasizing the importance of refining data and understanding the societal impact of OCA treatment. Addressing these aspects in future research can better inform healthcare decisions, prioritizing citizen well- being and societal benefits in the Philippine context.